- KEPEMIMPINAN ASTA BRATA DALAM MENGUATKAN IMPLEMENTASI KURIKULUM BERBASIS CINTA DI MADRASAH IBTIDAIYAH PROVINSI BALI - rahmi, wifqi (Adi Widya: Jurnal Pendidikan Dasar, 2025)
Kurikulum Berbasis Cinta (KBC) is a strategic initiative of the Indonesian Ministry of Religious Affairs aimed at restoring the humanistic dimension of education by strengthening compassion, empathy, and dignity-oriented relationships. This study aims to analyze how the values of Asta Brata—Surya, Candra, Agni, Bayu, Baruna, Kuwera, Yama, and Indra—can reinforce the implementation of KBC within Madrasah Ibtidaiyah (MI) in Bali Province. The method employed is a literature review, drawing upon classical philosophical texts, contemporary educational theories, and empirical studies on KBC, love pedagogy, and Asta Brata leadership. The findings indicate that integrating Asta Brata offers a systematic humanistic leadership framework, encompassing moral exemplarity (Surya), empathy and emotional well-being (Candra), pedagogical innovation (Agni), compassionate communication (Bayu), restorative conflict resolution (Baruna), equitable welfare distribution (Kuwera), ethical-based positive discipline (Yama), and comprehensive student protection (Indra). The study concludes that the synergy between Asta Brata and KBC produces a contextual, spiritual, and humanistic leadership model aligned with Balinese cultural values and the aims of twenty-first-century Islamic education. It further recommends developing Asta Brata–KBC leadership training programs for MI principals and conducting future studies in diverse madrasah settings.